2019
DOI: 10.1111/odi.13012
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the serum levels of galectin‐3 in patients with oral lichen planus disease

Abstract: Objectives Galectin‐3, a member of beta‐galactoside‐binding proteins, can be found in cytoplasm and nucleus as well as extracellularly in various tissues and involved in many physiological and pathological processes. We aimed to measure the serum levels of galectin‐3 in oral lichen planus (OLP) disease and compare the result with that observed in healthy ones. Materials and Methods In this cross‐sectional study, the serum levels of galectin‐3 were measured in 56 healthy individuals and 53 pathologically proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Our study found a significant immune expression of Gal-3 in A-ELP compared to the gingival overgrowth. This is consistent with the findings of Ghapanchi et al [ 27 ], who discovered substantial variations in serum Gal-3 (a member of the galectin family) levels between patients and healthy controls and proved Gal-3’s diagnostic capability for OLP. Also, erosive/atrophic forms had a higher Gal-3 concentration than reticular forms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study found a significant immune expression of Gal-3 in A-ELP compared to the gingival overgrowth. This is consistent with the findings of Ghapanchi et al [ 27 ], who discovered substantial variations in serum Gal-3 (a member of the galectin family) levels between patients and healthy controls and proved Gal-3’s diagnostic capability for OLP. Also, erosive/atrophic forms had a higher Gal-3 concentration than reticular forms.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in accordance with our results, elevated expression of Gal-3 was demonstrated in different types of oral lesions. In patients with salivary gland tumors, high serum level of Gal-3 was detected, and could moreover differentiate patients from the healthy individuals [ 27 ].…”
Section: Discussionmentioning
confidence: 99%